Red meat consumption and risk of type 2 diabetes: 3 cohorts of US adults and an updated meta-analysis - Pan, An; Sun, Qi; Bernstein, Adam M; Schulze, Matthias B; Manson, JoAnn E; Willett, Walter C; Hu, Frank B (The American journal of clinical nutrition, 2011)
The relation between consumption of different types of red meats and risk of type 2 diabetes (T2D) remains uncertain. We evaluated the association between unprocessed and processed red meat consumption and incident T2D in US adults. We followed 37,083 men in the Health Professionals Follow-Up Study (1986-2006), 79,570 women in the Nurses' Health Study I (1980-2008), and 87,504 women in the Nurses' Health Study II (1991-2005). Diet was assessed by validated food-frequency questionnaires, and data were updated every 4 y. Incident T2D was confirmed by a validated supplementary questionnaire. During 4,033,322 person-years of follow-up, we documented 13,759 incident T2D cases. After adjustment for age, BMI, and other lifestyle and dietary risk factors, both unprocessed and processed red meat intakes were positively associated with T2D risk in each cohort (all P-trend <0.001). The pooled HRs (95% CIs) for a one serving/d increase in unprocessed, processed, and total red meat consumption were 1.12 (1.08, 1.16), 1.32 (1.25, 1.40), and 1.14 (1.10, 1.18), respectively. The results were confirmed by a meta-analysis (442,101 participants and 28,228 diabetes cases): the RRs (95% CIs) were 1.19 (1.04, 1.37) and 1.51 (1.25, 1.83) for 100 g unprocessed red meat/d and for 50 g processed red meat/d, respectively. We estimated that substitutions of one serving of nuts, low-fat dairy, and whole grains per day for one serving of red meat per day were associated with a 16-35% lower risk of T2D. Our results suggest that red meat consumption, particularly processed red meat, is associated with an increased risk of T2D.